2017
DOI: 10.1007/s10648-017-9426-2
|View full text |Cite
|
Sign up to set email alerts
|

Extending Cognitive Load Theory to Incorporate Working Memory Resource Depletion: Evidence from the Spacing Effect

Abstract: Depletion of limited working memory resources may occur following extensive mental effort resulting in decreased performance compared to conditions requiring less extensive mental effort. This 'depletion effect' can be incorporated into cognitive load theory that is concerned with using the properties of human cognitive architecture, especially working memory, when designing instruction. Two experiments were carried out on the spacing effect that occurs when learning that is spaced by temporal gaps between lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(142 citation statements)
references
References 30 publications
(39 reference statements)
4
136
0
2
Order By: Relevance
“…Results showed that the one measure after the instruction or test phase was always higher than the average of multiple measurements during the learning or test phase. Although the exact reason for the difference is not clear, the higher single score after the learning or test phase could be suggestive for depletion of working memory resources (Chen et al 2018).…”
Section: Measuring Cognitive Loadmentioning
confidence: 97%
See 2 more Smart Citations
“…Results showed that the one measure after the instruction or test phase was always higher than the average of multiple measurements during the learning or test phase. Although the exact reason for the difference is not clear, the higher single score after the learning or test phase could be suggestive for depletion of working memory resources (Chen et al 2018).…”
Section: Measuring Cognitive Loadmentioning
confidence: 97%
“…A basic assumption of the principle has been that for any given individual, general working memory capacity is fixed. With recent evidence that working memory depletion occurs after cognitive effort and recovers after rest (Chen et al 2018), that assumption must be modified to allow such capacity variations. (This issue is discussed further in the 'Future Directions' section.…”
Section: Human Cognitive Architecture Seen Through the Prism Of Evolumentioning
confidence: 99%
See 1 more Smart Citation
“…24 Chen et al proposed to provide gaps between episodes of learning so that simultaneous interactions between multiple complex elements can be eased into the working memory. 25 Information presented to learners in the form of verbal, audio or video means are often transient (disappearing a few seconds after presentation) compared to the same in the form of written text or images. In the case of a long video or animation, learners will have to retain the information for a longer time in the working memory for processing which increases the cognitive load.…”
Section: A Reduce Extraneous Loadmentioning
confidence: 99%
“…These results notwithstanding, essentially all students were in a distributed practice condition, because practice in all groups was distributed across 19 days, and differences only reflect the effects of distribution within each day. In two experiments conducted by Chen, Castro‐Alonso, Paas, and Sweller (), fourth and fifth graders who practiced a mathematical procedure distributed over 3 days achieved higher performance scores than students who practiced massed on 1 day. However, for theoretical reasons, the authors varied the retention interval between the conditions: The massed‐practice students were tested immediately following the practice phase, whereas the distributed‐practice students were tested the day after their last practice session.…”
Section: Introductionmentioning
confidence: 98%